Incidental Enterobius Vermicularis infestation in surgically removed appendices with a clinical diagnosis of acute appendicitis: A retrospective analysis - P Upadhyaya; AK Sinha; M Agarwal; P Paudyal; A Shrestha (Association of Clinical Pathologists of Nepal, 2015)
Background: Appendiceal parasites can cause symptoms of appendicitis. Although the symptomatology imitates acute appendicitis clinically, the true nature of disease is diagnosed through histological examination. The aim of this study is to therefore determine the prevalence of E. Vermicularis in appendicectomy specimens to relate this to acute inflammation histologically. Materials & Methods: Histological data on all appendectomy specimens with a clinical diagnosis of acute appendicitis were retrieved from the archives of department of pathology, B.P.K.I.H.S, over the period of  five years (January 2004- December 2008) and was analyzed retrospectively. Results: There were a total of 1528 patients. M:F ratio being 1.2:1.Inflamed appendix constituted for 94.24% of all cases. There were a total of six (0.39%) appendicectomy specimens  which showed presence of oxyuriasis appendix. Though all patients with oxyuriasis presented with appendicial colic only one (1) out of the six cases of oxyuriasis showed histologic evidence of inflammation.  Conclusion: We conclude that enterobius does not frequently cause inflammation of appendix though it may clinically mimic acute appendicitis. Since it represents a disease curable without necessitating surgery, symptomatology awareness is stressed upon. Journal of Pathology of Nepal (2015) Vol. 5, 720-722